Understanding the Role of Organizational Culture in Knowledge Management in Micro, Small and Medium Enterprises - Budi Rismayadi (INFOKUM, 2024)
Organizational culture has a significant impact on how knowledge is organized, shared and utilized in the MSME environment. This research aims to explore the role of organizational culture in the context of knowledge management in micro, small and medium enterprises (MSMEs). This research uses a qualitative approach with descriptive methods. The research results show that organizational culture plays a central role in the effectiveness of knowledge management at the Micro, Small and Medium Enterprises (MSME) level. A culture that supports collaboration, innovation, and learning creates an environment that supports the exchange of ideas, integration of individual knowledge, and social interaction among MSME team members. Leaders who understand and support the organization's culture are key to stimulating successful knowledge management practices. By wisely utilizing organizational culture, MSMEs can improve operational efficiency, stimulate innovation, and compete effectively in dynamic markets, which in turn increases the competitiveness and sustainability of their businesses.